Genetic diversity among commercial coffee varieties, advanced selections and museum collections in Kenya using molecular markers - Gichimu, Bernard M.; Kathurima, CW.; Kenji, GM.; Muhoho, SM.; Boulanger, R.; Gichuru, E. K. (Academic Journals, 2012)
Molecular markers have effectively been applied to study genetic diversity and as markers of particular traits. This study assessed the diversity of twenty four (24) coffee genotypes using 10 Random Amplified Polymorphic DNA (RAPD) primers and 2 microsatellites (M24 and Sat 235). A total of 35 polymorphic bands were generated by the RAPD primers. The bands were scored for presence (1) and absence (0) of amplified products. The data was subjected to cluster analysis using R statistical software and a dendrogram constructed using Unweighted Pair Group Method with Arithmetic Average (UPGMA). The genotypes separated into three main clusters. C. eugenioides clustered alone in the first cluster while un-introgressed Arabica genotypes dominated the second cluster. The third cluster comprised of Coffea canephora (Robusta) and introgressed genotypes, Ruiru 11, Hibrido de Timor and Catimor. Robusta and C. eugenioides were the most distantly related and generated most of the diversity observed. The similarities observed among un-introgressed Arabica genotypes attest to the narrow genetic diversity within Coffea arabica. The divergence observed among introgressed genotypes could be utilized in future breeding programmes.
Keywords: Coffee accessions; RAPD; microsatellites; diversity; Kenya